Selected Lectures of the 3rd S.I.P.Ped. International Congress; Milan (Italy); November 29 - December 1, 2022 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the 3rd S.I.P.Ped. International Congress • QUALITY OF LIFE AND ASSISTANCE OF MINOR WITH CHRONIC DISEASE: FROM PRE-BIRTH TO ADOLESCENCE • Milan (Italy) • November 29th - December 1st, 2022    LECT 1. THE EXPERIENCE OF PEDIATRIC PSYCHOLOGY IN MATERNAL AND CHILD DEPARTMENT • G. Perricone, C. Polizzi (Palermo, Italy)  LECT 2. PEER RELATIONSHIPS AND ADOLESCENTS WITH CHRONIC DISEASE • A.M. La Greca (Coral Gables, FL, USA)  LECT 3. PARENTAL ETHNOTHEORIES AND CHILD CARING IN MIGRANT FAMILIES • G.G. Valtolina (Milan, Italy)  LECT 4. THE CENTRALITY OF THE CHRONIC CHILD IN ACCOMPANIMENT TO TREATMENT • G. Ragni, P. Becherucci, M. Lo Giudice, M. Picca (Latina, Florence, Palermo and Milan, Italy)  LECT 5. THE PEDIATRIC PSYCHOLOGIST IN DERMATOLOGICAL CHRONICITY. MULTIDISCIPLINARY WORK EXPERIENCE IN THE CLINIC OF ATOPIC DERMATITIS • A. Dattolo (Rome, Italy)  LECT 6. COULD THE NUTRITION OF THE PREGNANT WOMAN PREVENT DIFFERENT FORMS OF CHRONICITY? • F. Caturano (Turin, Italy)  LECT 7. QUALITY OF LIFE AND CARE OF A CHILD WITH CHRONIC PATHOLOGY: FROM PRE-NATAL LIFE TO ADOLESCENCE • F. Monti (Bologna, Italy)  LECT 8. TO CARE OF THE MINOR WITH NEURODEVELOPMENTAL DISORDERS IN THE TRANSITION TO THE ADULT PHASE • M.R. Morales (Varese, Italy)  LECT 9. THE POWER OF EPIGENETICS IN PERINATALITY • V. Fanos (Cagliari, Italy)